Cardiac Autonomic Dysfunction in Obstructive Sleep Apnea : The Hidden Role of Vitamin D Deficiency - Huai Heng, Loh; Siow Phing, Tay; Ai Jiun, Koa; Mei Ching, Yong; Asri, Said; Chee Shee, Chai; Natasya Marliana, Abdul Malik; Anselm, Su Ting; Bonnie Bao Chee, Tang; Florence Hui Sieng, Tan; Norlela, Sukor (John Wiley & Sons Australia, Ltd, 2025)
Obstructive sleep apnea (OSA) is a common sleep-breathing disorder, affecting an estimated 9–38% of adults worldwide, with prevalence increasing in parallel with rising obesity rates and aging population [1]. While men are still more likely to be diagnosed with OSA, this condition is becoming more common in women [2]. Coronary artery disease (CAD), a common complication of OSA, is driven by a combination of intermittent hypoxia, metabolic dysfunction, and systemic inflammation, which together accelerate atherosclerosis [3]. This underscores the importance of identifying modifiable factors to mitigate cardiovascular risks in these patients. A key mechanism linking OSA to heightened cardiovascular risks in CAD is cardiac autonomic dysfunction, characterized by increased sympathetic activity and reduced parasympathetic tone. These alterations can be assessed through heart rate variability (HRV), a well-established predictor of adverse cardiovascular outcomes.